Strategi Pengembangan Kualitas Layanan Digital dalam Membentuk Kepuasan Nasabah BSI Sidoarjo - Surahmah, Surahmah (Saneskara: Journal of Social Studies, 2024)
The rapid advancement of technology has transformed the banking industry, enabling the introduction of digital services that simplify customer transactions. This progress has intensified competition among banks to deliver high-quality services aimed at enhancing customer satisfaction, retaining existing clients, and attracting new ones. Customer satisfaction is achieved when banks provide accessible, high-quality services that meet customer expectations. This study examines the quality of digital services provided by BSI Mobile Banking and its role in shaping customer satisfaction at BSI Sidoarjo. A qualitative descriptive method was employed, utilizing interviews, observations, and documentation for data collection. The findings reveal that BSI Mobile Banking offers one of the most comprehensive digital banking features compared to other digital services. It not only supports financial transactions but also includes Islamic financial features that simplify banking activities for customers. By utilizing BSI Mobile, customers can conduct transactions independently without visiting bank branches or ATMs. Strategies to enhance digital service quality—such as upgrading technological infrastructure, developing user-friendly mobile banking applications, and providing customer training—have significantly contributed to customer satisfaction at BSI Sidoarjo and increased the adoption of BSI Mobile services. The practical implications of this research underscore the importance of prioritizing the development of high-quality digital services to enhance customer satisfaction and loyalty, ensuring banks remain competitive in the digital era.